2009
DOI: 10.1097/chi.0b013e3181bfd669
|View full text |Cite
|
Sign up to set email alerts
|

Medication and Parent Training in Children With Pervasive Developmental Disorders and Serious Behavior Problems: Results From a Randomized Clinical Trial

Abstract: Objective Many children with Pervasive Developmental Disorders (PDDs) have serious, functionally-impairing behavioral problems. We tested whether Combined Treatment (COMB) with risperidone and parent training (PT) in behavior management is superior to Medication alone (MED) in improving severe behavioral problems in children with PDDs. Method This 24-week, three-site, randomized, parallel-groups clinical trial enrolled 124 children, aged 4 through 13 years, with PDDs, accompanied by frequent tantrums, self i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
205
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 285 publications
(215 citation statements)
references
References 40 publications
(40 reference statements)
6
205
0
4
Order By: Relevance
“…Finally, there are few studies that have directly and appropriately compared psychotropics with psychosocial interventions. For example, although an RCT by Aman et al 77 demonstrated that combining risperidone with training from parents produced better child outcomes than risperidone alone, the trial did not include a group that only received parent training.…”
Section: Autism Spectrum Disordersmentioning
confidence: 99%
“…Finally, there are few studies that have directly and appropriately compared psychotropics with psychosocial interventions. For example, although an RCT by Aman et al 77 demonstrated that combining risperidone with training from parents produced better child outcomes than risperidone alone, the trial did not include a group that only received parent training.…”
Section: Autism Spectrum Disordersmentioning
confidence: 99%
“…For example, Triple P has been modified for use with parents of children with ID (Stepping Stones Triple P; Plant & Sanders, 2007) and Parent-Child Interaction Therapy has been applied to parents of children with ID (Bagner & Eyberg, 2007). Other similar behavioral parent training programs have been designed and developed specifically for families of children with ID or autism spectrum disorder, such as Signposts for Better Behavior (Hudson et al, 2003) and the RUPP Parent Training program (Aman et al, 2009). Each of these intervention programs has produced meaningful reductions in child problem behavior.…”
Section: Parent Training Strategiesmentioning
confidence: 99%
“…AP reduce maladaptive behaviors, such as irritability, self-injury, stereotypies, and hyperactivity, in children and adolescents with ASD, and reduce irritability and aggressive behavior in children and adolescents with disruptive behavior disorder (DBD) (2).…”
Section: Introductionmentioning
confidence: 99%